2004
DOI: 10.1136/gut.2003.020503
|View full text |Cite
|
Sign up to set email alerts
|

The Department of Health's "two week standard" for bowel cancer: is it working?

Abstract: Objective: To determine the effectiveness and efficiency of the Department of Health's new general practitioner referral guidelines for bowel cancer. Design: One year prospective audit. Setting: District general hospital serving a population of 550 000. Subjects: All patients with bowel cancer; all patients referred on the basis of the two week standard and to a routine colorectal surgical outpatient clinic. Main outcome measures: Proportion of cancers referred on the basis of the two week standard and to othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
107
1
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(114 citation statements)
references
References 12 publications
3
107
1
3
Order By: Relevance
“…5,12,28 Moreover, the 57 % incidence of rectal bleeding and change in bowel habits in bowel cancer was very similar to 58 and 51% in a symptomatic colorectal study. 13 In our study, 92.8% of all cancers were within the reach of the sigmoidoscope and 7.2% were on the right side which is in keeping with previous reports. 29 Unexplained weight loss, peri-anal pain and passing mucus per rectum were the most significant independent predictors of colorectal carcinoma in our symptomatic population.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…5,12,28 Moreover, the 57 % incidence of rectal bleeding and change in bowel habits in bowel cancer was very similar to 58 and 51% in a symptomatic colorectal study. 13 In our study, 92.8% of all cancers were within the reach of the sigmoidoscope and 7.2% were on the right side which is in keeping with previous reports. 29 Unexplained weight loss, peri-anal pain and passing mucus per rectum were the most significant independent predictors of colorectal carcinoma in our symptomatic population.…”
Section: Discussionsupporting
confidence: 80%
“…19 Most patients referred to secondary centres with colorectal cancers have more than one symptom (85%). 13 Furthermore, these symptoms are subjected to selection bias which affects their predictive value in both the primary and secondary care settings. 20 Rectal bleeding is one of the most widely known and feared symptom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted in Portsmouth has shown that 74% of 249 cases of colorectal cancer were diagnosed by a route other than the Two Week Wait Rule clinics. 10 The diagnostic yield for this route is not good either. Although higher than the final diagnostic yield obtained via routine clinics (2%), a systematic review of studies performed in England and Wales showed that, out of 2440 patients referred using the Two Week Wait Rule, only 10.3% were subsequently diagnosed with colorectal cancer.…”
mentioning
confidence: 99%
“…There were seventeen case series that involved 38-3119 patients, two rcts that included 478 and 791 patients, and one case-control study that included 177 cases and 162 controls 4,7,[15][16][17][18][19][20][21][22][23][24][25][26][31][32][33][34][35][36] . The update of the literature search identified 823 citations in which patient outcomes related to diagnostic assessment units were described for colorectal cancer in four studies [27][28][29][30] , head-and-neck cancer in two studies 37,38 , lung cancer in two studies 39,40 , gynecologic cancers in three studies [41][42][43] , neurologic cancers in one study 44 , lymph node cancers in one study 45 , and upper gastrointestinal cancers in one study 46 . Study designs included one small rct (88 patients), seven prospective cohort studies (359-3637 patients), and six retrospective studies (69-930 patients) [27][28][29][30][37][38][39][40][41][42]…”
Section: Search Resultsmentioning
confidence: 99%